BIMBINGAN KARIR BERBASIS KEAGAMAAN OLEH LAKPESDAM NU DAN KOMUNITAS MAKARYA DALAM MENGATASI PEMUDA PENGANGGURAN - Husni, M Zakaria (Dakwah, 2017)
The Makarya community is one of the youth communities that shelters the needs of unemployed youth. During this time, the Makarya Community has joined hands with Lakpesdam NU Lumajang to carry out unemployment handling programs. This study aims to find out how guidance is used in overcoming unemployment. This study uses qualitative methods with a Case Study approach. The study shows that Career Guidance based on religious services by Lakpesdam NU and the Makarya Community in dealing with unemployed youth, that is, inviting unemployed youth  by guiding them to understand and evaluate themselves, and then realize and understand the values within themselves and their communities, know the work environment related to their potential, find and be able overcome obstacles, and lastly plan for the future of his career. Religious-based Career Guidance, Lakpesdam NU, Youth Unemployment, Makarya Community.